The effect of different nanocatalysts for photocatalytic degradation of methylene blue - Pala, Ayşegül (Array, 2019)
The aim of this study was to investigate photodegradation of Methylene Blue (MB) in water by using ZnO and TiO2 nanoparticles. Adsorption and photocatalytic oxidation studies were carried out by using produced TiO2, commercial TiO2 and commercial ZnO nanoparticles. In order to evaluate performance tests, 5 mg/l of MB solution was used. The samples were mixed in the dark for 2 hours for establishing adsorption-desorption equilibrium. The photocatalytic tests of the samples were performed by assessing the decomposition rate of MB solutions under UV light. The results of the photocatalytic showed that the highest color removal efficiencies was obtained by TiO2 catalyst where Methylene blue solution was completely degraded.